ICT Innovations 2014 world of data - ICT Innovations (Conference) Ohrid, Macedonia) 2014; Bogdanova, Ana Madevska; Gjorgjevikj, Dejan; SpringerLink (Online service). (Cham Springer International Publishing, 2015)
This book offers a collection of selected papers presented at the Sixth International Conference on ICT Innovations held in September 2014, in Ohrid, Macedonia, with main topic World of data. The conference gathered academics, professionals and practitioners in developing solutions and systems in the industrial and business arena, especially innovative commercial implementations, novel applications of technology, and experience in applying recent ICT research advances to practical solutions.
Electronic reproduction.
Keywords: Data mining -- Congresses; Databases -- Congresses; Information storage and retrieval systems -- Congresses